Model Penerapan Strategi Storytelling Public Relations Dalam Promosi Budaya Lokal - Zon Vanel; Lina Sinatra Wijaya (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2026)
This study aims to analyze and formulate a Public Relations (PR) storytelling strategy model in promoting local culture, specifically keris as a Javanese cultural heritage in Surakarta. Keris, recognized by UNESCO as an intangible cultural heritage, faces serious challenges, including declining interest among younger generations, limited regeneration of empu (traditional keris craftsmen), and the lack of optimal utilization of digital media in cultural promotion. This research employed a descriptive qualitative approach through in-depth interviews with empu, lecturers, and students of the Keris Study Program at ISI Surakarta, digital content observation, and questionnaires distributed to the public. The findings reveal that PR storytelling strategies through transactional storytelling, experiential storytelling, and narrative persuasion significantly enhance audience engagement, emotional connection, and public brand awareness toward keris culture. The implementation of digital storytelling campaigns on Instagram and TikTok successfully encouraged active audience participation through challenges, testimonial videos, and persuasive narrative content. Furthermore, this study proposes a new cultural communication framework called the Kerisverse Campaign Model, which integrates participatory interaction, authentic experiences, and emotional narratives within a digital ecosystem. The model is considered effective in strengthening local cultural preservation, positioning keris as a living heritage, and increasing youth involvement in digital-based cultural preservation efforts.